Anti–forensic steganography using multi–bit MER with flexible bit location. (6th March 2015) - Chen, Rong–Jian; Horng, Shi–Jinn; Huang, Po–Hsian
This work develops an anti–forensic steganography system using the proposed multi–bit MERs with flexible bit location embedding method (multi–bit MER_FBL embedding method) to overcome the problem of forensics and to achieve high performance including both large embedding capacity and high image quality. The proposed multi–bit MER_FBL embedding method hides multi–bit (k–bit, k ≥ 1) logo/secret data into any adjoining (starting with the ith location) k–bit bi bi−1 bi−k+ of cover data only introduces MEE in the range of 0 to ±(2 k - 1)2 i−k ; moreover, its flexible bit location enhances the embedded security as security increases as the embedding location closing to the MSBs of cover data. We thus develop a thresholding mechanic to evaluate the anti–forensics degree of the proposed method. Finally, antiforensics of the proposed steganography systems are demonstrated using the visual attack and the statistical attack of Chi–square analysis.